2018
DOI: 10.1021/acs.jpca.7b12348
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation of Protonated Asparagine–Valine Investigated by a Combined Spectroscopic, Guided Ion Beam, and Theoretical Study

Abstract: Peptide deamidation of asparaginyl residues is a spontaneous post-translational modification that is believed to play a role in aging and several diseases. It is also a well-known small-molecule loss channel in the MS/MS spectra of protonated peptides. Here we investigate the deamidation reaction, as well as other decomposition pathways, of the protonated dipeptide asparagine–valine ([AsnVal + H]+) upon low-energy activation in a mass spectrometer. Using a combination of infrared ion spectroscopy, guided ion b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 57 publications
(140 reference statements)
3
31
0
Order By: Relevance
“…Therefore, in the current work, we establish the likely mechanisms for possible deamidation processes of protonated AsnSer ([AsnSer+H] + ), identify the deamidation product(s) formed, and evaluate the reaction threshold for deamidation via infrared (IR) action spectroscopy and threshold collision-induced dissociation (TCID) experiments, coupled with theory. This work complements analogous studies conducted previously on [AsnXxx+H] + for Xxx = Gly, 16 Ala, 17,18 Val, 19 and Thr. 20 Succinimide intermediate formation as a result of Asn deamidation is well-documented in the literature; 1,2,21 however, given the intrinsic differences between a dipeptide and a protein as well as between gas-phase and condensedphase reactivity, we have also explored alternative pathways that may exist for ammonia loss.…”
Section: ■ Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, in the current work, we establish the likely mechanisms for possible deamidation processes of protonated AsnSer ([AsnSer+H] + ), identify the deamidation product(s) formed, and evaluate the reaction threshold for deamidation via infrared (IR) action spectroscopy and threshold collision-induced dissociation (TCID) experiments, coupled with theory. This work complements analogous studies conducted previously on [AsnXxx+H] + for Xxx = Gly, 16 Ala, 17,18 Val, 19 and Thr. 20 Succinimide intermediate formation as a result of Asn deamidation is well-documented in the literature; 1,2,21 however, given the intrinsic differences between a dipeptide and a protein as well as between gas-phase and condensedphase reactivity, we have also explored alternative pathways that may exist for ammonia loss.…”
Section: ■ Introductionsupporting
confidence: 86%
“…16 The deamidation of [AsnAla+H] + proceeds along bifurcating pathways resulting in the observation of both Fur and Suc structures, 17,18 whereas the deamidation of [AsnVal+H] + results exclusively in the formation of a Fur structure. 19 In contrast, the deamidation of [AsnThr+H] + leads predominantly to the formation of a Suc product ion, 20 with a minor contribution of Fur. Thus, the current results, compared with our previous analyses of [AsnGly+H] + , [AsnAla+H] + , [AsnVal +H] + , and [AsnThr+H] + , should allow for the determination of C-terminal residue side-chain effects with respect to both size and side-chain functionality.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, tightening the vibrational frequencies below 900 cm –1 (those tagged by Gaussian 16 as potentially inaccurate) of the tight TSs by ∼25% is sufficient to bring the TCID thresholds into agreement with the theoretical values for H 2 O and CO 2 loss from (O) p-ABAH + and for H 2 O + CO 2 loss from (N)-p-ABAH + . This extent of scaling for TS frequencies is precedented in several studies conducted on the dissociation behavior of small protonated di- and tripeptides, where scaling factors of 22–32% were needed in order to quantitatively predict the relative magnitudes and energetics for competing dissociation pathways. , For BAH + , the low-frequencies for the TSs leading to H 2 O and CO 2 loss require tightening by ∼50% in order to yield quantitative agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Various (spectroscopic) studies on the dehydration of protonated dipeptides not containing a Ser or Thr residue showed that water is expelled from the C-terminal carboxylic acid group. ,,,, This reaction is suggested to proceed via a nucleophilic attack on the C-terminal carboxylic acid carbon generating a b 2 -type sequence ion, which can have either an oxazolone or a diketopiperazine structure. In contrast, for the Thr and Ser terminal peptides studied here, an alternative mechanism is at work.…”
Section: Resultsmentioning
confidence: 99%